The Genus Athyrium Roth in Malesia : A Checklist With Working Names and Distributions - Wardani, Wita; Adjie, Bayu (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2018)
Athyrium Roth is a terrestrial fern genus in Athyriaceae, mostly distributed in temperate and sub-tropical regions. In Malesia, this genus is confined to higher altitudes. We have scrutinised the names listed in the literature as well as those used from specimens housed in herbaria that are possibly true Athyrium. Of the 25 species names, 12 are attributed to the Philippines, eight are recognised from Java and seven from Borneo and Sumatra. Other parts of Malesia contribute fewer species. A list of names together with information on distribution and specimens examined is provided.